(untitled) (Journal of Educational Sciences, 2016)
In psycho-pedagogical science is interested in the cognitive theorists, the question of how to organize the educational process in order to enhance the thinking process and efficiently help to learn and to give the students knowledge. The researchers found that 80% of people learn better when I see clearly, i.e. visually. The teacher who adheres to the educational process patterns and didactic principles of visual presentation, achieves the best results, even when mastering of complex theoretical material. Since the filing of didactic material has its own quirks and psycho-pedagogical mechanisms of visual perception, activating cognitive process of students. The article discusses the design features of didactic presentations from the point of view of psycho– pedagogical patterns and learning principles of presentation, i.e. the Golden rule in didactics first proposed in the work «Didactics» of Czech teacher Jan Amos Kamensky. In the organization of the didactic structure of electronic presentation it is important to consider presenting in the educational process, the following elements: business card, plan, time, title of the picture or slide, associative image, consistency and integrity of the completeness of the information, content information, volume information, the location information on the page. It is important to adhere to the laws of visual perception: the figure and the background, first line indent, key words, colors, animations, fonts, changing pictures and slides, further reading, strategy, questions and answers, teaching methods of attracting attention, supporting the activation of the entire viewing period (early, mid, late), video and audio materials. The nature of the stimulation of students in class is derived from a structured and logical–sequential electronic didactic presentations that help to systematically present all material omprehensively, thus forming system vision and thinking. The process of generating a sensual perspective image forming direction, and the internal motivation of the subjects, the direction of flow. As a complete presentation students can at home according to their individual personality view, repeat and independent work of the student under the guidance of a teacher may consult, ask questions extracurricular time if not cared or missed the point. Ignoring the psycho–pedagogical patterns in the construction of the didactic structuring of electronic material by the teacher in class can affect the performance and not give positive results in learning as the lesson in the learning process focuses students on the subject of cognitive activity focuses on verbal cognitive activity and creates a verbal context modeling in General.